THE EFFECT OF THE HEALTH CARE INFECTION CONTROL COMMITTEE IN PATIENTS WITH URINARY CATHETERS ON COST CONTAINMENT - Amirah, Asriwati; Fitriani, Arifah Devi; Suarayasa, Ketut; Suharto, Teguh; Asepty, M.Rizky Priyanka (BRIN - Badan Riset dan Inovasi Nasional, 2024)
The high prevalence of healthcare-associated infections threatens hospital services. Urinary tract infections associated with the use of catheters could reach 0.2–4.8 per 1000 catheters/day. In response to this, the Centers for Disease Control and Prevention recommends using the Healthcare Infection Control Practices Advisory Committee (HICPAC) to reduce the incidence of infection in hospitals. To determine the effect of implementing HICPAC on reducing hospital costs for patients with urinary catheters at Delia Hospital, Langkat Regency, in 2019. At the Delia General Hospital in Langkat Regency, Malaysia, quantitative research using a quasi-experimental technique was carried out, in which all patients with urinary catheters were included as respondents. The paired t-test was used to evaluate the data using SPSS software. The results revealed a significant effect of the HICPAC application on the incidence of Catheter-Associated Urinary Tract Infection (CAUTI) in patients during treatment (p = 0.08). The HICPAC method can also reduce the risk of CAUTI by 3.902 times. This study did not evaluate the morbidity and mortality attributable to CAUTI. An assessment of the length of stay, cost analysis, and antibiotic resistance is needed to assess the benefits of the HICPAC guidelines. The use of HICPAC in patients with urinary catheters can reduce the cost of treatment at Delia Hospital, Langkat Regency.